MOBILE SMARTPHONE INTERVENTION FOR MANAGING GLYCAEMIA CONTROL IN THE PATIENTS WITH DIABETES MELLITUS: A SYSTEMATIC REVIEW - Tifanny Gita Sesaria; Kusnanto Kusnanto; Abu Bakar (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Diabetes mellitus (DM) is a chronic disease that is a global public health problem that has a social impact, economic impact, and quality of life for patients, which leads to increased morbidity and mortality. Uncontrolled blood sugar levels and long-term DM, affecting the pathophysiology of disorders including diabetic retinopathy, heart disease, kidney failure, hyperglycemia and hypoglycemia are needed interventions that can help regulate glycemic (blood sugar levels and HbA1c) (Sami & Ansari, 2015).Objective: This study aimed to identify efficacy mobile smartphone application for managing glycaemia control in the patients with diabetes mellitus.Design: This study design is a systematic review to search and review article from database and the theory underlying this study or guidance in this systematic literature review using Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA).Data Sources: Database search for article are from Scopus, Proquest, Pubmed, Science Direct, and Springer Link is limited to the publication of the last five years from 2015 to 2020 and full text article in English.Review Methods: This review methods in a systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA).Results: In this review literature, thirteen articles were found that fit the specified inclusion and exclusion criteria. The results of this review literature found that mobile smartphone impelmentation led to a decrease in HbA1c and fasting blood glucose in the patients with diabetes mellitus.Conclusion: The findings from this study help validate the efficacy of the mobile diabetes intervention for managing glycaemia control in the patients with diabetes mellitus. Keywords: Diabetes Mellitus, Glycaemia Control, Health Education, M-Health.